2016
DOI: 10.1038/srep37753
|View full text |Cite
|
Sign up to set email alerts
|

Selection for predation, not female fecundity, explains sexual size dimorphism in the orchid mantises

Abstract: Here we reconstruct the evolutionary shift towards floral simulation in orchid mantises and suggest female predatory selection as the likely driving force behind the development of extreme sexual size dimorphism. Through analysis of body size data and phylogenetic modelling of trait evolution, we recovered an ancestral shift towards sexual dimorphisms in both size and appearance in a lineage of flower-associated praying mantises. Sedentary female flower mantises dramatically increased in size prior to a transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 56 publications
0
21
1
Order By: Relevance
“…All the traits scaled allometrically with pronotum length (Figure 3, Table 1), a common measure of body size among arthropods (Svenson et al, 2016). These results are in contrast to an intraspecific study on Stagmomantis theophila that showed isometric growth of the forelegs in relation to body mass (Sutton, Doroshenko, Cullen, & Burrows, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…All the traits scaled allometrically with pronotum length (Figure 3, Table 1), a common measure of body size among arthropods (Svenson et al, 2016). These results are in contrast to an intraspecific study on Stagmomantis theophila that showed isometric growth of the forelegs in relation to body mass (Sutton, Doroshenko, Cullen, & Burrows, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…When possible, I included both males and females, measuring 1–3 individuals per sex, per species. While there is dimorphism in some mantis species (Svenson et al, 2016), I averaged males and females as none of the specimens measured represented known major dimorphic species. Furthermore, because some species had only one sex to measure, or the sex was unclear, averaging the sexes better represented the interspecific diversity.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Representatives of Chaeteessidae and Mantoididae were included to root the phylogeny based on their consistent recovery as the two earliest branches of Mantodea (Svenson and Whiting 2009, Wieland 2013, Svenson et al 2015). We assembled a molecular dataset from previously published works (Svenson and Whiting 2004, 2009, Svenson et al 2016) and newly generated sequence data (see Table 1 for GenBank accession numbers). The molecular dataset included four genes: the mitochondrial cytochrome oxidase I (COI) and NADH dehydrogenase subunit 4 (ND4) and the nuclear Histone subunits 2 and 3 (H2A and H3).…”
Section: Methodsmentioning
confidence: 99%